PSIII-5 Delaying Weaning Age of Lambs Grazing Chicory (Cichorium Intybus) Increases Body Weight - Campbell, Braden J (J Anim Sci, 2021)
Two common challenges in forage-based lamb production systems is the restriction of net energy from grass-based pastures and the production losses associated with parasitic infection. The inclusion of nutrient rich forage in the diet and delaying lamb weaning age has shown to improve lamb growth rates in some systems. The objective of this experiment was to investigate the effects of grazing chicory (Cichorium intybus) and delayed weaning on the growth and health of young pasture-raised lambs. We hypothesized that improving the quality of available forage and delaying weaning would increase the body weight and parasite resilience of lambs. A total of 18 cross-bred ewes and 36 cross-bred lambs (25.2 ± 0.5 kg) were stratified by weight, sex, and randomly assigned to one of two weaning treatments: lambs weaned at 60 days of age (weaned) and lambs remained with their dam and weaned at 120 days of age (delayed weaned). Data were analyzed using PROC MIXED in SAS. Lamb body weight and indices of parasitism were measured every 14 days. There was a treatment × day effect for body weight as delayed weaned lambs were heavier on days 28, 42, and 56 compared with the body weight of weaned lambs (P < 0.02). In addition, there was a treatment × day effect for average daily gain (ADG) whereas delayed weaned lambs demonstrated greater ADG on days 14, 28, 42, and 56 compared with the ADG of weaned lambs (P < 0.02). In monitoring lamb health, there was a treatment × day effect as weaned lambs had a greater packed cell volume (PCV) on day 14 compared with the PCV of delayed weaned lambs (P < 0.03). Conversely, on day 56, weaned lambs had a lower PCV compared with the PCV of delayed wean lambs (P < 0.004). Delayed weaning has shown to be beneficial in improving lamb growth; however, in this instance, delayed weaning demonstrated variable responses in supporting lamb health while grazing on improved pastures.